2019
DOI: 10.14202/vetworld.2019.823-829
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of lactic acid bacteria in dadih produced by either back-slopping or spontaneous fermentation from two different regions of West Sumatra, Indonesia

Abstract: Aim: Dadih samples from two different origins (Kamang and Gadut in West Sumatra) manufactured with different methods (back-slopping or spontaneous fermentation) were evaluated for the diversity of lactic acid bacteria (LAB). Materials and Methods: Four dadih samples manufactured with two different fermentation methods were obtained from Kamang and Gadut regions. Both genotypic and phenotypic characteristic (16S rRNA partial gene sequence analysis and carbohydrate fermentation profile) were used to analyze the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
4

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 36 publications
1
29
0
4
Order By: Relevance
“…The study by Melia et al (2018) on buffalo milk samples from the Agam district (BMA 3.3) showed the LAB as a strain of L. fermentum (L23) using BLAST analysis. Wirawati et al (2019) reported sequence results in dadiah from two different regions of West Sumatra that showed 41.6% (five isolates) were identified as Lactococcus lactis ssp. lactis, 25% (three isolates) identified as Lactobacillus plantarum ssp.…”
Section: Molecular Identification By 16s Rrna Methodsmentioning
confidence: 99%
“…The study by Melia et al (2018) on buffalo milk samples from the Agam district (BMA 3.3) showed the LAB as a strain of L. fermentum (L23) using BLAST analysis. Wirawati et al (2019) reported sequence results in dadiah from two different regions of West Sumatra that showed 41.6% (five isolates) were identified as Lactococcus lactis ssp. lactis, 25% (three isolates) identified as Lactobacillus plantarum ssp.…”
Section: Molecular Identification By 16s Rrna Methodsmentioning
confidence: 99%
“…plantarum, L. lactis ssp. cremoris, Pediococcus pentosaceus, and Lactobacillus pentosus are some types of bacteria that are naturally found in curd (Wirawati et al (2019). Tempoyak, a natural fermentation product from Durian, is also a natural fermentation product (Juliyarsi et al (2018) and tempoyak also contains lactic acid bacteria that have the potential as probiotics (Hartini et al 2019 andAhmad et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, these manufacturing accidents offer an interesting model for microbiologists to study the dispersion and resilience of microbial communities. Various mesophilic fermented milks have been described among dairy products [3] and include Vilii in Finland, Dahi in India or Dadih in Indonesia, whose process is similar to that of Gwell [11]. They are obtained after a thermization step of the milk, by inoculation of a previous day production.…”
Section: Introductionmentioning
confidence: 99%